Cryptocurrencies: A survey on acceptance, governance and market dynamics. (14th December 2020) - Hairudin, Aiman; Sifat, Imtiaz Mohammad; Mohamad, Azhar; Yusof, Yusniliyana
Abstract: This paper briefly overviews several challenging dimensions pertaining to cryptocurrencies with respect to their valuation, legitimacy, design, consensual acceptance and market‐based stylized facts with a view to understanding whether this new asset class indeed has the potential to become an alternative, or a replacement, to traditional fiat currencies. Our survey indicates that public embrace of cryptocurrencies continues to lag as the masses currently show reluctance in embracing cryptocurrencies as a complement, let alone a substitute to fiat counterparts. Governments have also successfully defended their sovereignty in preserving legal tender status, structural seigniorage and exclusivity. Market‐based studies hint at consistent inefficiencies across the spectrum. Furthermore, whether fundamental and mining factors determine cryptocurrencies' values remain unsettled. The most promising areas of research for crypto‐financial intelligentsia would be delving into establishing trial runs for central bank‐backed cryptocurrencies. In addition, we highlight that several methodological and data‐based obstacles remain in assessing the link between cryptocurrencies and their traditional rivals. This avenue remains a fertile ground for potential future research.